Pendugaan Standard Error dan Confidence Interval Koefisien Gini dengan Metode Bootstrap: - Dwi Indri Arieska; Novi Hidayat Pusponegoro (Jurnal Aplikasi Statistika & Komputasi Statistik, 2016)
Income inequality is one of economic development indicators. As a kind of inequality indicators which is commonly used in Indonesia, gini coefficient is published as a point estimation. This estimation are lacking in its function as an estimator because it doesn’t considerate the probability accuration of the estimate value.Thus, the confidence interval estimation is needed as a comprehensive estimator. The objective of this study is estimate the standard errors and confidence intervals Gini coefficients with the bootstrap method. This study used National Social Economics Household Survey for West Papua Province in 2013. The Gini coefficient that used is a bias-corrected gini coefficient as consideration the bias in the calculation. The standard error of bias-corrected gini coefficient in West Papua is carried out of two data, which are the original sample and resample nonparametric bootstrap method. This research found out that bootstrap-t confidence interval confidence interval is the best confidence interval since it has the smallest standard error and shortest interval.